Correlation of diuretic therapy toward clinicaloutcomeof patients suffering from chronic kidney disease hospitalized in RSUP DR. M. Djamil Padang - Sani K., Fathnur; Nazar, Armenia; Haque, Aina Fatkhil (Universitas Ahmad Dahlan, 2018)
ABSTRACTKidney is one of the most important organs of the human body. The goal of diuretic therapy is to reduce edema in patients with impaired renal function. The therapy of diuretic is very important, because the therapy is effective to control of the volume of extracellular fluid, reduce protein exretion in urine and reduce on effects of hyperceluler complications. The purpose of this research is to provide information on the effect of giving diuretics with clinical outcome of patient with cronic kidney disease. The research was conducted by using longitudinal observational study design. Longitudinal observation is a method that perform data retrieval by a prospective census method with daily follow up until patient returns. The result of research showed that the most widely used diuretic was furosemide. Then the results also showed improvement of blood pressure, pulse, respiration rate, creatinine and urea although the results were not statistically significally (p>0.05). Mortality rate of the subjects in RSUP DR. M.Djamil Padang Hospital was very small. Patient with diuretic and without diuretic have equal mortality rate (p>0.05).Keyword: Kidney, CKD, Outcome, Diuretic